World’s Top 2% Scientists List (career-long) - Agapiou, Athos (My University, 2026)
“World’s Top 2% Scientists List”, Included among the top 2% of highly cited scientists in the world, career-long (Baas, Jeroen; Boyack, Kevin; Ioannidis, John P.A. (2021), “August 2021 data-update for "Updated science-wide author databases of standardized citation indicators"”, Mendeley Data, V3, doi: 10.17632/btchxktzyw.3 Updated science-wide author databases of standardized citation indicators)
Keywords: Sciences